Paeoniflorin Ameliorates Chronic Hypoxia/SU5416-Induced Pulmonary Arterial Hypertension by Inhibiting Endothelial-to-Mesenchymal Transition - Yu M; Peng L; Liu P; Yang M; Zhou H; Ding Y; Wang J; Huang W; Tan Q; Wang Y; Xie W; Kong H; et al. (Dove Medical Press, 2020)
Min Yu,1,* Liyao Peng,1,* Ping Liu,1 Mingxia Yang,2 Hong Zhou,1 Yirui Ding,1 Jingjing Wang,3 Wen Huang,1 Qi Tan,1 Yanli Wang,1 Weiping Xie,1 Hui Kong,1 Hong Wang1 1Department of Respiratory and Critical Care Medicine, The First Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu 210029, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, The Affiliated Changzhou No.2 People’s Hospital of Nanjing Medical University, Changzhou 213003, People’s Republic of China; 3Department of Respiratory Medicine, Shanghai Pulmonary Hospital, Tongji University School of Medicine, Shanghai 200433, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hui Kong; Hong WangDepartment of Respiratory and Critical Care Medicine, The First Affiliated Hospital of Nanjing Medical University, 300 Guangzhou Road, Nanjing, Jiangsu 210029, People’s Republic of ChinaTel +86-25-68136426Fax +86-25-68136269Email konghui@njmu.edu.cn; hongwang@njmu.edu.cnBackground: Endothelial cells dysfunction is one of the hallmark pathogenic features of pulmonary arterial hypertension (PAH). Paeoniflorin (PF) is a monoterpene glycoside with endothelial protection, vasodilation, antifibrotic, anti–inflammatory and antioxidative properties. However, the effects of PF on PAH remain unknown.Methods: Here, we investigated the efficacy of PF in the SU5416/hypoxia (SuHx) rat model of PAH. Human pulmonary arterial endothelial cells (HPAECs) were exposed to 1% O2 with or without PF treatment.Results: Hemodynamics analysis showed that prophylactic treatment with PF (300 mg/kg i.g. daily for 21 days) significantly inhibited chronic hypoxia/SU5416-induced elevations of right ventricular systolic pressure (RVSP) and right ventricular hypertrophy index in rats. Meanwhile, PF significantly reduced pulmonary vascular remodeling, as well as alleviated collagen deposition in lungs and right ventricles in SuHx rats. Additionally, PF inhibited SuHx–induced down-regulation of endothelial marker (vascular endothelial cadherin) and up-regulation of mesenchymal markers (fibronectin and vimentin) in lung, suggesting that PF could inhibit SuHx–induced endothelial-to-mesenchymal transition (EndMT) in lung. Further in vitro studies confirmed that PF treatment suppressed hypoxia-induced EndMT in HPAECs, which was abolished by the knockdown of bone morphogenetic protein receptor type 2 (BMPR2) in HPAECs.Conclusion: Taken together, our findings suggest that PF ameliorates BMPR2 down-regulation-mediated EndMT and thereafter alleviates SuHx–induced PAH in rats.Keywords: paeoniflorin, pulmonary arterial hypertension, endothelial-to-mesenchymal transition, BMPR2, hypoxia